An exploratory LC‐MS‐based metabolomics study reveals differences in aqueous humor composition between diabetic and non‐diabetic patients with cataract. Issue 9 (19th January 2018) - Pietrowska, Karolina; Dmuchowska, Diana Anna; Krasnicki, Pawel; Bujalska, Aleksandra; Samczuk, Paulina; Parfieniuk, Ewa; Kowalczyk, Tomasz; Wojnar, Malgorzata; Mariak, Zofia; Kretowski, Adam; Ciborowski, Michal
Abstract: Cataract is the leading cause of blindness worldwide. Epidemiological studies revealed up to a fivefold increased prevalence of cataracts in diabetic subjects. Metabolomics is nowadays frequently implemented to understand pathophysiological processes responsible for disease occurrence and progression. It has also been used recently to study the metabolic composition of aqueous humor (AH). AH is a transparent fluid which fills the anterior and posterior chambers of the eye. It supplies nutrients and removes metabolic waste from avascular tissues in the eye. The aim of this study was to use metabolomics to compare the AH of diabetic and non‐diabetic patients undergoing cataract surgery. Several antioxidants (methyltetrahydrofolic acid, taurine, niacinamide, xanthine, and uric acid) were found decreased (−22 to −61%, p ‐value 0.05–0.003) in AH of diabetics. Also amino acids (AA) and derivatives were found decreased (−21 to −36%, p ‐value 0.05–0.01) while glycosylated AA increased (+75–98%, p ‐value 0.03–0.009) in this group of patients. Metformin was detected in AH of people taking this drug. To our knowledge, this is the first metabolomics study aiming to assess differences in AH composition between diabetic and non‐diabetic patients with cataract. An increased oxidative stress and perturbations in amino acid metabolism in AH may be responsible for earlier cataract onset in diabetic patients.